1985
DOI: 10.1159/000194835
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moderately Elevated Levels of Carboxyhemoglobin on the Course of Acute Ischemic Heart Disease

Abstract: The purpose of this prospective study in 66 patients with acute ischemic heart disease was to analyze the possible effects of moderately elevated levels of carboxyhemoglobin (COHb) on the early course of this disease. Thirty-one patients presented with a level of COHb ≤2% and 35 with a level of > 2%. In the group with elevated COHb, more patients developed transmural infarction, but the difference was not significant (p = 0.123). Patients with transmural infarction had higher maximum CPK values (p < 0.01), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Many researches have done earlier in smoking subjects found that NRT in smoking cessation have no significant disturbances of autonomic cardiac control (including heart rate, systolic blood pressure, hematologic and coagulation indices, and CO level) when compared with smoking event in smokers [ 20 23 ]. However, this did not mean NRT is safe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researches have done earlier in smoking subjects found that NRT in smoking cessation have no significant disturbances of autonomic cardiac control (including heart rate, systolic blood pressure, hematologic and coagulation indices, and CO level) when compared with smoking event in smokers [ 20 23 ]. However, this did not mean NRT is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, excessive energy demands on the system Note: data was presented as mean ± SEM; "F" meant female, "M" meant male; LF and HF measurements were in normalized unit; only P value < 0.05 was annotated. Many researches have done earlier in smoking subjects found that NRT in smoking cessation have no significant disturbances of autonomic cardiac control (including heart rate, systolic blood pressure, hematologic and coagulation indices, and CO level) when compared with smoking event in smokers [20][21][22][23]. However, this did not mean NRT is safe.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…In a single blind, crossover, placebocontrolled study, high-dose nicotine patch along with cigarette smoking had no additional adverse effects on heart rate, blood pressure, fibrinogen levels, or lipid profiles in long-term smokers [14]. The probable explanation is the development of tolerance to nicotine and hence minimal CVD events in long-term smokers who received NRT [15,21,22].…”
Section: Nicotine Replacement Therapymentioning
confidence: 99%
“…The reported blood COHb level is approximately 1.0% in non-smokers and 5.5% in patients with a smoking history (10). In some studies, it has been reported that high and low COHb levels are associated with poor clinical prognosis in various pathological conditions, including pulmonary embolism (PTE), acute ischemic heart disease, and critically ill patients in intensive care units (ICU) (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%